Pemanfaatan Limbah Bubur Kopi (Coffee pulp) dalam Budidaya Perikanan (Review) - Diamahesa, Wastu Ayu; Muahiddah, Nuri (Journal of Fish Nutrition, 2023)
From several decades ago until today, coffee consumption has been a cultural norm. Coffee pulp (CP) is a byproduct of the initial separation of husks or seeds from coffee fruits. The increase in coffee production will lead to an increase in CP residues and refuse, which, if left unchecked, will result in environmental issues. Several previous studies have attempted to address this waste by focusing on organic fertilizer products, enhancing soil conditions, biological control, animal feed, and human sustenance. However, only a small number of researchers have conducted studies utilizing CP, and most of them have not been successful in incorporating this raw material into fish nutrition. Consequently, the purpose of this review is to characterize the potential of CP in the field of aquaculture so that additional research can be conducted using this raw material.